2020
DOI: 10.3390/diagnostics10080571
|View full text |Cite
|
Sign up to set email alerts
|

Regional Mapping of Brain Glutamate Distributions Using Glutamate-Weighted Chemical Exchange Saturation Transfer Imaging

Abstract: Purpose: To investigate glutamate signal distributions in multiple brain regions of a healthy rat brain using glutamate-weighted chemical exchange saturation transfer (GluCEST) imaging. Method: The GluCEST data were obtained using a 7.0 T magnetic resonance imaging (MRI) scanner, and all data were analyzed using conventional magnetization transfer ratio asymmetry in eight brain regions (cortex, hippocampus, corpus callosum, and rest of midbrain in each hemisphere). GluCEST data acquisition was performed again … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The 10% GA treatment showed hair growth and angiogenesis stimulation, but no differences in Hif1a expression after 14 day of topical GA. Previous studies showed the ranges of GA saturation by specific GA concentration [42][43][44] . In this way, we suggest that 10% GA topical treatment could achieve a post-acute signal saturation secondary to the time exposure and the Glutamic Acid concentration here presented.…”
Section: Discussionmentioning
confidence: 98%
“…The 10% GA treatment showed hair growth and angiogenesis stimulation, but no differences in Hif1a expression after 14 day of topical GA. Previous studies showed the ranges of GA saturation by specific GA concentration [42][43][44] . In this way, we suggest that 10% GA topical treatment could achieve a post-acute signal saturation secondary to the time exposure and the Glutamic Acid concentration here presented.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, numerous studies have been proposed for detecting neurochemical signals such as Glu [ 55 ], mIns [ 56 ], Cr [ 57 ], and GABA [ 19 ] compounds, using the chemical exchange saturation transfer (CEST) technique. CEST imaging is a novel contrast enhancement technique that enables the indirect measurement of molecules with exchangeable solute protons [ 58 ]. Thus, CEST imaging with specific metabolites will be suitable for better understanding the molecular mechanism of cerebral demyelination in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical exchange saturation transfer (CEST) technique is a relatively recent advancement in MRI [26,[28][29][30]. This method involves the application of a frequency-selective radiofrequency (RF) irradiation pulse to specific exchangeable protons (such as hydroxyls, amides, and amines) [31,32].…”
Section: Introductionmentioning
confidence: 99%